The risk of coerced confession in the plea mechanism and its implications for corruption cases - Jason Thimoty Silitonga (Integritas: Jurnal Antikorupsi, 2026)
The integration of guilty plea mechanisms into Indonesia's reformed Code of Criminal Procedure (KUHAP) raises fundamental questions regarding the tension between procedural efficiency and the integrity of substantive truth-seeking, particularly in corruption cases that demand comprehensive evidentiary processes to expose systemically structured criminal networks. This study employs normative legal research utilizing statutory, conceptual, and comparative approaches, supported by analysis of primary legal materials, academic literature, and cross-jurisdictional examination of plea bargaining practices across common law and civil law systems. The analysis reveals that the special track mechanism under Law No. 20 of 2025 structurally generates conditions conducive to coerced confession, as negotiations between prosecutors and defendants unfold within an inherently asymmetric power relationship. In corruption cases, this risks producing guilty pleas driven by legal risk calculation rather than factual acknowledgment, potentially halting evidentiary processes before criminal networks are fully exposed  a risk compounded in multi-defendant scenarios where asymmetric use of plea mechanisms may produce evidentiary fragmentation and inconsistent judicial outcomes. Effective implementation requires operationalization through subordinate regulations, strengthened independent judicial verification of confession voluntariness, and inter-institutional coordination to safeguard evidentiary coherence in collective corruption cases.